Fitz-Hugh-Curtis syndrome: a case study of a frequently missed diagnosis - Zephania D. P. Gega; Henry I. Lyimo; Daniel W. Kitua; Ally H. Mwanga (Journal of Rare Diseases)
Abstract Introduction Fitz-Hugh-Curtis syndrome (FHCS) is a relatively common complication of pelvic inflammatory disease. However, this diagnosis is frequently overlooked due to its nonspecific symptomatology that often mimics hepatobiliary disorders. This report presents a case of FHCS and offers a review of pertinent clinical considerations. Case We describe a case of a 33-year-old sexually active female previously treated for vaginal discharge syndrome, who presented to our facility with worsening right upper quadrant pain. Initial laboratory and imaging findings were inconclusive. However, diagnostic laparoscopy revealed perihepatic “violin string” adhesions consistent with FHCS. Conclusion This case underscores the importance of considering FHCS in the differential diagnosis of right upper quadrant pain, especially in individuals with a history of pelvic inflammatory disease. Awareness of this syndrome and its clinical manifestations is crucial for prompt diagnosis and appropriate management.